Shoesfit: Augmented reality mobile commerce application for shoes fitting / Umar Faiz Danial Ibrahim - Ibrahim, Umar Faiz Danial (2019)
Online shopping has been a key part of our shopping activity. It makes shopping more time-saving and gives customers more choices. The most obvious disadvantage of online shopping, however, is that the customer cannot be face-to-face with the products while selecting them. Augmented Reality (AR) is a technology that combines the virtual world with the real world. Users are able to have an "immersive" shopping experience with the assist of augmented reality technology. Users and the environment have clear natural interactions. Thus, this project's purpose is to provide a new unique and innovative way to improve customer’s shopping experience specifically in shopping for shoes online by combining mobile commerce and augmented reality technology. ShoesFit is a 3D Augmented Reality app that allows users to virtually try on shoes before deciding to buy the shoes. This app enables the users to fit the shoes on their feet virtually with the implementation of Marker-based Augmented Reality. This project aims at identifying user requirements for ShoesFit's mobile commerce application, designing the ShoesFit mobile commerce application, and development of the ShoesFit mobile commerce application. This project will be using the android platform. The target user of this project would be the people in Shah Alam who uses a mobile application for online shopping and also online local retailers that utilized mobile commerce platform to advertise their products. Mobile Application Development Lifecycle (MADLC) is the approach employed to complete this task. The augmented reality technique utilized in this project is the marker-based augmented reality. Combined with 3-Dimensional object recognition, this project emphasizes virtualized shoes on the user’s feet by pointing the smartphone’s camera to the feet of the user. In the future, this project is recommended to include the mobile payment gateway instead of online banking so that the purchasing transaction will become more hassle-free. In a nutshell, ShoesFit mobile commerce application able the enrich the shopping experience of the users with the emergence of advanced technology.